VD_FINDINFO Jug / 2012 / 212 vom 13. Februar 2012 - VD Tribunal cantonal (2012)
LÉSION CORPORELLE SIMPLE, FIXATION DE LA PEINE, INJURE, MENACEDROIT PÉNAL, COAUTEURDROIT PÉNAL | 123 ch. 1 CP, 177 al. 1 CP, 180 al. 1 CP, 42 CP, 47 CP, 49 al. 2 CP